THE SOCIAL CONSEQUENCES OF USING DESTRUCTIVE TECHNOLOGIES IN PR COMMUNICATIONS - Mastura Khaitova (Journals Park Publishing, 2023)
The article analyzes the concept of PR and its importance, its formation as a separate area, methods of full and effective transmission of information to the target audience using PR technologies, destructive PR technologies, their application and social consequences.
Keywords: Рublic relations, Communications, PR Technologies, Media, destructive PR technologies